Effect of Source and Novel Host Plants on Twospotted Spider Mites - Burgett, Haley; Nechols, James (My University, 2017)
A laboratory experiment was conducted to determine how well spider mite populations would develop on different host plants, and if the source plant the mite was reared on would affect their performance on other plants. This study was important because twospotted spider mite is a notorious pest on many greenhouses and household plants, but different plants may not be equally suitable for mite development and survival. The main question in my study was: Does the host plant have a significant effect on spider mite population growth? My results showed no difference in mite population numbers based on which colony plant mites were reared on. However, they tended to do better on marigold, which was a new host plant, than on their source plants – lima bean and cotton. This experiment is important because it helps us determine the level of damage risk from spider mites on different plants, and also if a new host plant is more or less likely to experience high pest populations. My results differed from a previous study (Gould 1978) which showed that twospotted spider mites had lower survival on new host plants compared to the one on which they had been reared.